Indoor positioning techniques using RSSI from wireless networks - Sohan, Asif Ahmed; Fairooz, Fabiha; Rahman, Adham Ibrahim; Ali, Mohammad (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.